Effectiveness of Risk Management Strategies in Mitigating Supply Chain Disruptions in South Africa - Enzokuhle, Grace (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to examine the effectiveness of risk management strategies in mitigating supply chain disruptions in South Africa Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The effectiveness of risk management strategies in mitigating supply chain disruptions in South Africa has proven to be critical in maintaining operational stability and ensuring business continuity. In an environment characterized by frequent economic, political, and environmental challenges, robust risk management strategies have become indispensable for South African businesses. These strategies, including risk assessment, diversification of suppliers, implementation of advanced technologies, and development of contingency plans, have significantly enhanced the resilience of supply chains. By systematically identifying and evaluating potential risks, businesses have been able to proactively address vulnerabilities and reduce the impact of disruptions. The use of advanced technologies, such as predictive analytics, real-time monitoring systems, and blockchain, has further strengthened risk management efforts. These technologies provide valuable insights into supply chain dynamics, enable early detection of potential disruptions, and facilitate rapid response measures. As a result, businesses can maintain smoother operations and minimize downtime during unforeseen events. Unique Contribution to Theory, Practice and Policy: Resilience Theory, Resource-Based View (RBV) & Contingency Theory may be used to anchor future studies on effectiveness of risk management strategies in mitigating supply chain disruptions in South Africa. Encourage the adoption of advanced technologies such as Internet of Things (IoT), artificial intelligence (AI), and blockchain for real-time monitoring and supply chain visibility. Practical implementation of these technologies can enhance early detection of disruptions and facilitate rapid response strategies. Foster closer collaboration with suppliers to co-develop robust contingency plans and risk-sharing mechanisms. Practices such as dual sourcing, supplier diversification, and joint risk assessments can build resilience across the supply chain network. Advocate for policies that incentivize resilience-building practices within supply chains. This could include tax incentives for investments in resilient infrastructure, as well as mandatory reporting on supply chain risk management practices to enhance transparency and accountability.